Evaluation of Residual Root Height and Width for The Fabrication of Rai in South India Population - S, Hamitha; Selvaganesh, Sahana; Nesappan, Thiyaneshwar (Journal of Neonatal Surgery, 2025)
Introduction: The precision and accuracy of the study can be significantly improved by using cone beam computed tomography (CBCT) into the assessment of residual root height and width for the manufacture of ROOT Analogue Implants (RAI) in the South Indian population. Comprehensive study of the residual root anatomy is made possible by the detailed three-dimensional images of the oral and maxillofacial tissues that are provided by CBCT imaging. Researchers can quantify residual root dimensions, such as height and width, with high resolution and little distortion by using CBCT. This makes it possible to precisely plan the placement of implants, accounting for elements including bone density, closeness to surrounding structures, and the best location for stability and aesthetics over the long run. Materials And Method: A substantial and reliable sample size that can offer important insights into the anatomical features and suitability for implant placement in the South Indian population is the selection of a cohort of 300 patients for CBCT testing in the context of dental implants. Results: A substantial and reliable sample size that can offer important insights into the anatomical features and suitability for implant placement in the South Indian population is the selection of a cohort of 300 patients for CBCT testing in the context of dental implants. Conclusion: To sum up, the incorporation of CBCT technology in the assessment of residual root dimensions improves the precision and efficacy of RAI fabrication for the South Indian populace, hence leading to improved clinical results and patient care.